PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT MAJAPAHIT DIAN SELARAS TANGERANG SELATAN - Daniel Bagas Danurwenda; Muhamad Guruh (Journal of Research and Publication Innovation, 2025)
This study aims to determine the Influence of Work Discipline and Work Motivation on Employee Performance at PT Majapahit Dian Selaras Tangerang Selatan. The method used in this study is the quantitative associative method. The population in this study were all employees as many as 56 respondents. The sampling technique in this study was the saturated sampling technique or all members of the population were sampled. Data analysis used validity tests, reliability tests, classical assumption tests, coefficient tests, linear regression tests, hypothesis tests. The results of this study are that Work Discipline (X1) has a positive and significant effect on Employee Performance (Y) with a regression value of Y = 19.068 + 0.484 X1. The correlation value is 0.542 where the value has a moderate level of relationship. The determination or contribution value is 0.294 or 29.4% while the remaining 70.6% is influenced by other factors. And the results of the hypothesis test (t test) obtained a value of tcount> ttable or (4.744> 2.005). Thus H01 is rejected and Ha1 is accepted, meaning that there is a positive and significant influence between Work Discipline (X1) on Employee Performance (Y) at PT Majapahit Dian Selaras Tangerang Selatan. Work Motivation (X2) has a positive and significant influence on Employee Performance (Y) with a regression value of Y = 14.013 + 0.632 X2. The correlation value is 0.709 where this value has a strong level of relationship. The determination or contribution value is 0.503 or 50.3% while the remaining 49.7% is influenced by other factors. And the results of the hypothesis test (t test) obtained a value of tcount> ttable or (7.392> 2.005). Thus H02 is rejected and Ha2 is accepted, meaning that there is a positive and significant influence between Work Motivation (X2) on Employee Performance (Y) at PT Majapahit Dian Selaras Tangerang Selatan. Work Discipline (X1) and Work Motivation (X2) have a positive and significant effect on Employee Performance (Y) with a regression value of Y = 12.710 + 0.103 X1 + 0.563 X2. The correlation value is 0.714 where the value has a strong level of relationship. The determination or contribution value is 0.510 or 51% while the remaining 49% is influenced by other factors. And the results of the hypothesis test (f test) obtained tcount> ttable or (27.593> 2.779). Thus H03 is rejected and Ha3 is accepted, meaning that there is a positive and significant effect between Work Discipline (X1) and Work Motivation (X2) simultaneously on Employee Performance (Y) at PT Majapahit Dian Selaras Tangerang Selatan.